IMPLEMENTASI PENANGANAN PENGEMIS DI KOTA PEKANBARU TAHUN 2023 - Salmadina, Dhifa; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
ABSTRACT The increase in the number of beggars in Pekanbaru City not only has an impact on public order and welfare, but also poses challenges in the enforcement of policies regulated by the government. Regional Regulation of Pekanbaru City No. 12/2008 on Social Order was formulated as a policy in dealing with the problem of begging. Although the handling in this regulation has been implemented, the reality is that the number of beggars in Pekanbaru City continues to increase, especially in the last three years, with a significant increase occurring in 2023. Therefore, this research aims to find out how the Implementation of Handling Beggars in Pekanbaru City in 2023. In this study, the theory used is the Theory of Policy Implementation from Gorge C. Edward III. The method used in this research uses a qualitative approach with descriptive research type. The data collection method in this study was carried out by interview and documentation. The results showed that the Social Service Office, as part of the government responsible for handling beggars based on the Pekanbaru City Regional Regulation Number 12 of 2008 concerning Social Order, has not implemented the policy optimally. This is caused by several factors, including the delivery of policy messages that are still limited and not comprehensive, the absence of a special budget allocation for handling beggars, the absence of incentives for policy implementers, and the gap between policy implementation and the provisions listed in the regulation, so that many provisions in the regulation are considered unrealized. With this research, it is hoped that the Social Service can increase efforts in implementing Regional Regulations that become Policies in Handling Beggars to be more optimal and as an implementor the Social Service needs to coordinate with the government regarding policy provisions that cannot be implemented, this can include proposals for improvements or revisions to regulations. Keywords : Implementation, Handling, Regional Regulations, Beggar